Cuneiform Texts in Australian Public Collections: Phase One Complete - Siddall, Luis R. (Buried History: The Journal of the Australian Institute of Archaeology, 2016)
Cuneiform texts in Australia and New Zealand are being published by a team of scholars. This paper reports on the progress of the work in Australian and lists the material discovered in public collections thus far.